Fungsi Adverbial Bahasa Melayu Manado - Nurdin, Anas Yuliadi (Universitas Sam Ratulangi, 2015)
The purpose of this study was to determine the structure of adverbialin Malay Manado. The data collection method using the method followed by thetechnique refer to note. This study is a library that makes the writings of ManadoMalay language as the main data is supported by the method of introspection toget valid data. In this study adverbial structures tested by testersinterrogative sentence and adverbial placement in the sentence structure. The adverbial structures Manado Malay language consists of words, phrases, and clauses.Key words: the adverbial, structures, Manado Malay language.